Direct Amplification of B1 gene of Toxoplasma gondii DNA using Nested Polymerase Chain Reaction Following Microwave Treatment for Whole Blood Samples: Balkes Fadel hade¹; Abdulameer Mohamed Ghareeb² and May Hameed Kawan - hade, Balkes Fadel (The Iraqi Journal of Veterinary Medicine, 2015)
Infection with Toxoplasma gondii is a cause of fetal death since T. gondii can be transmitted to the fetus through the placenta (transplacental) from an infected mother or at vaginal delivery. Blood obtained from women and sheep to confirm their infection with toxoplasmosis by using Enzyme Linked Immunosorbant Assay test (ELISA) to ditective positive specific anti-Toxoplasma (IgM, IgG and IgM, or IgG) antibodies. This study used two methodes to extract DNA (the first one was a standard extraction commercial method (CM-PCR) of genomic DNA using a commercial kit (Promega, USA), and the second one was the direct heat DNA extraction using microwave oven (MW-PCR) for whole blood samples obtained from infected women and sheep. Then nested Polymerase Chain Reaction (n PCR) were used to amplify Toxoplasma B1 gene to detect T. gondii DNA in whole blood samples. The results indecated using of microwave treatment instead of commercial kit to extract DNA is low cost and short time,and complement serology for clinical studies and diagnostic purposes of toxoplasmosis.